Reopening a Criminal Case Due to a Clearly Improper Application of Criminal Law: The Development of Legal Regulation and Some Problems - Kuconis, Pranas (Teisė, 2022)
This paper reveals reasons for the resumption of a criminal case due to a clearly improper application of norms pertaining to criminal law. It indicates the main concepts of this institute and problems of legal regulation and proposes solutions.